Endoplasmic reticulum stress is involved in lipopolysaccharide‐induced inflammatory response and apoptosis in goat endometrial stromal cells. Issue 7 (1st May 2019) - Mohamed, Amira Abdalla Abdelshafy; Yang, Diqi; Liu, Shouqin; Lin, Pengfei; Mohamad, Osama Abdalla Abdelshafy; Jin, Yaping
Abstract: Endoplasmic reticulum (ER) stress is involved in regulating cell metabolism, apoptosis, autophagy, and survival. However, there is not enough information about the role of ER stress in lipopolysaccharide (LPS)‐induced apoptosis and inflammatory cytokine secretion in the uterus. In this study, we found that LPS induced apoptosis and inflammation in goat endometrial stromal cells (ESCs). LPS treatment inhibited cell viability and cell proliferation. In addition, the genes associated with proliferation, such as proliferating cell nuclear antigen and MKI67, were affected by LPS treatment. Moreover, LPS increased the secretion of interleukin (IL)‐1β and IL‐8, promoting the levels of MYD88, caspase1, and TRL4. The 4‐phenylbutyric acid pretreatment inhibited the expression of unfolded protein response proteins and the secretion of inflammatory cytokines in LPS‐treated cells. However, blockage of inositol‐requiring enzyme 1 and activating transcription factor 6 did not significantly reduce apoptosis and inflammatory cytokine secretion. Collectively, ER stress involved in LPS‐induced apoptosis and inflammatory cytokine increased in goat ESCs. This study provides new insight into the function of ER stress in the pathological process.